A revision of the spider genus Echinax Deeleman-Reinhold, 2001 (Araneae: Corinnidae) in the Afrotropical Region - Haddad, Charles R. (Zootaxa, 2012)
The cryptic arboreal castianeirine genus Echinax Deeleman-Reinhold, 2001 (Araneae: Corinnidae), previously known only from South-East Asia, is recorded from the Afrotropical Region for the first time. The female of Copa longespina Simon, 1909 is redescribed, the male is described for the first time, and the species is transferred to Echinax as E. longespina (Simon, 1909) comb. nov. It occurs widely throughout equatorial Africa, from Kenya and Tanzania in the east to Liberia in the west. Six new species are described from both sexes: E. clara sp. nov. from D.R. Congo and Ghana, E. hesperis sp. nov. from Ivory Coast, E. natalensis sp. nov. and E. similis sp. nov. from South Africa, E. scharffi sp. nov. from Tanzania, and E. spatulata sp. nov., widespread across tropical Africa. The available ecological data indicates that all seven species are mainly arboreal and represent a prominent component of corinnid assemblage collected by canopy fogging, especially in forests.